Configurationally stable dithia[7]helicene and dithia-quasi[8]circulene fused dithiolones. Issue 16 (20th June 2022) - Baudillon, Maxime; Cauchy, Thomas; Vanthuyne, Nicolas; Avarvari, Narcis; Pop, Flavia
Abstract : Stereochemically stable dithia[7]helicene and dithia-quasi[8]circulene decorated with 1, 3-dithiol-2-one motifs were synthesized by simple and double oxidative dehydrocyclisation. Abstract : Dithia-[7]helicene and quasi[8]circulene have been formed on the 1, 3-dithiol-2-one ring by oxidative dehydrocyclisation of bis-naphthothiophenyl-1, 3-dithiol-2-one. Quasi-circulenes are easily obtained at room temperature by successive dehydrocyclisations regardless the amount of oxidation reagent whereas selectivity towards helicene, involving a single dehydrocyclisation, has been achieved only at low temperature. DFT calculations suggest a mechanism via a dication intermediate rather than a mono-cation for the formation of the quasi-circulenes whereas the helicene should be formed via a radical cation intermediate. While dithia[7]helicene is known to give stable stereoisomers, here the unsubstituted dithia-quasi[8]circulene shows unprecedented configurational stability of the enantiomers, with a theoretically estimated enantiomerisation energy barrier of 30.4 kcal mol −1, in excellent agreement with the experimentally determined value of 29.8 kcal mol −1 . The enantiomers of both helicene and quasi-circulene have been separated by chiral chromatography and their absolute configuration assigned from the calculated CD spectra.